Diagnoses and management of adult cough: An Indian Environmental Medical Association (EMA) position paper. (July 2020) - Shankar, P.S.; Korukonda, K.; Bendre, S.; Behera, D.; Mirchandani, L.; Awad, N.T.; Prasad, R.; Bhargava, S.; Sharma, O.P.; Jindal, S.K.
Abstract: Background: Cough is a common yet distressing symptom that results in significant health care costs from outpatient visits and related consultations. Objective: The understanding of the pathobiology of cough in recent times has undergone an evolution with Cough hypersensitivity syndrome (CHS) being suggested in most cases of dry cough. However, in the case of productive cough, ancillary mechanisms including impaired Mucociliary clearance, in addition to hypermucosecretory bronchospastic conditions of Smoker's cough, asthma-COPD overlap, bronchiectasis, and allergic bronchopulmonary aspergillosis, need to be critically addressed while optimizing patient care with symptomatic therapy in outpatient settings of India. Methods: In this review, evidence-based graded recommendations on use of antitussives - & protussives as a Position Paper were developed based on the Level and Quality of Scientific evidence as per Agency for Health Care and Quality (AHRQ) criteria listing and Expert opinions offered by a multidisciplinary EMA panel in India. Results: Management of acute or chronic cough involves addressing common issues of environmental exposures and patient concerns before instituting supportive therapy with antitussives or bronchodilatory cough formulations containing mucoactives, anti-inflammatory, or short-acting beta-2 agonist agents. Conclusion: The analyses provides a real world approach to the management of acute or chronic cough in various clinical conditions with pro- or antitussive agents while avoiding their misuse in empirical settings. Highlights: Real world approach on diagnosis and management of chronic cough with anti- or protussive formulations. Pragmatic algorithmic approach for assessment of acute and chronic cough phenotypes. Mucociliary clearance is impacted in Bronchiectasis, cystic fibrosis, chronic bronchitis, asthma or ACO and ABPA. Chronic dry cough involving Cough hypersensitivity syndrome is often amenable to treatment with antitussive with complimentary actions. Bronchodilators offer mechanistic reasoning for improvement of mucociliary clearance for evaluation in productive cough management.